The influence of the processes of digitalization of the economy on the activities of non-financial institutions - G. N. Ryazanova; A. A. Sazanova; S. L. Sazanova (Управление)
The driver of the modern global economy is digital technologies under the influence of which not only new kinds of professions, goods and services are formed, but also challenges for enterprises and the organization of various fields of activity. Digitalization affected the IT-sphere, the activities of financial organizations, production, marketing, healthcare. In the Russian Federation the development of digital technologies in various fields of activity is of great importance, which is reflected in official documents, targeted government programs, business analysts and business practices. All this actualizes the study of the problem of management transformation in non-financial organizations under the influence of the spread of digital technologies.The article examines the strategic challenges facing non-financial organizations of Russia in the digital economy. In the course of solving the tasks set, the formation and development of the digital economy, its essence and content, as well as the prospects for its development in our country, were studied; the program documents and directions of the state program for the development of the digital economy are analyzed. It is proved that involvement in the digitalization processes of not only financial but also non-financial organizations carries a huge potential in terms of improving the value environment of Russian business, since it makes transactions in the shadow economy, corruption schemes, etc. transparent. The authors have proved that the revival of traditional values of Russian entrepreneurship on a new modern basis will increase the level of trust in society, will promote the development of innovations in industry, energy, agro-industrial complex, education and sustainable development of the economy as a whole. The authors structured the challenges of the digital economy for non-financial organizations in our country and formulated proposals for improving the ecosystem of the digital economy.